Reproductive Performance Of Bali Cattle Cross Breed Brahman Cattle Through Improving The Genetic Quality Of Local Livestock In Special Effort for Cows to be Pregnant Program - Irwansyah; Junaedi; Suparman (Program Studi Peternakan Fakultas Sains dan Teknologi Universitas Muhammadiyah Sinjai, 2021)
One of the problems that exist in the community is the lack of identification of the reproductive performance of prospective brooders of Bali cattle that are artificially inseminated. The researcher conducted a research to determine the reproductive performance of Bali Cattle inseminated with Brahman Cattle Semen in SECP (Special Effort for Cows to be Pregnant Program) Program in Kolaka Regency. The parameters observed in this study were; artificial insemination's first age (Years), How many times the artificial insemination (AI) was pregnant (S/C), Length of pregnancy (months), Calving Interval (CI) (months), Birth weight (Kilograms), Correlation of AI's first age with birth weight. Sources of date used in this study are primary and secondary data. Data collection techniques carried out in this study were observation and interviews. The date obtained was analyzed descriptively, analysis of variance, average, and to calculate the relationship between variables was analyzed by correlation. Reproductive performance of Bali Cattle inseminated with Brahman Cattle Semen in SECP Program in Kolaka district include; first age AI 23.63±1.99 months, Service per Conception (S/C) 1.56±0.55, gestational age 9.03±0.38 months, Calving Interval (CI) 12.24±0 .52 months, birth weight 27.85 ± 2.96 and the correlation between AI prime age and birth spacing was 0.77.